Impact of genetic selection and enhanced feeding on growth rate of Nilagiri and Sandyno sheep and their lambs - KUMAR, R ANIL; PREMA, N; VENKATARAMANAN, R; PRABHAKAR, R (The Indian Journal of Animal Sciences, 2022)
Weaned ewe lambs born during 2009-2014 were ranked according to their breeding value ascertained by BLUP analysis for weaning weight. Ten weaned ewe lambs each in Nilagiri and Sandyno breeds, on the top of the ranking were selected each year and placed as a separate elite group and were supplemented with increased level of concentrate feed from weaning with 8 h of routine grazing. Weight at 6, 9 and 12 months was recorded. Weight at birth, weaning, 6th and 12th months of lambs born to elite ewes were recorded up to February 2020 lambing. The data were analyzed by least square analysis. The body weight at 6, 9 and 12 months of age were significantly higher in elite ewes (17.22±0.21, 22.17±0.24, 26.19±0.27 vs 14.29±0.10, 18.09±0.13, 21.38±0.14). Elite Sandyno lambs weighed significantly higher than elite Nilagiri lambs at all stages. Highest ADG was observed in Sandyno elite ewe lambs during 6 months to 9 months period (62.98±2.80 g). The ADG was significantly higher in elite ewes during this period and from 9 months to 12 months (54.79±1.85 and 44.38±1.61 vs 37.52±0.98 and 33.70±0.87). The average birth weight, weaning weight and weaning percentage of born elite Nilagiri lambs (2.88±0.15, 11.52±0.77 and 93.54% vs 2.63±0.15, 10.02±0.76 and 90.82%) and Sandyno lambs (3.41±0.17, 12.91±0.86 and 94.69% vs 3.04±0.17, 11.31±0.84 and 91.73%) were significantly higher. The survivability of twin lambs was significantly higher in born elite lambs. The findings will help in promoting genetic selection and improved nutritional management in sheep farms from weaning to improve growth rate, better lamb crop and good survivability. Marginal increase in the feed would bring a substantial improvement in the performance of the sheep.